A Review of PARP-1 Inhibitors: Assessing Emerging Prospects and Tailoring Therapeutic Strategies - Ramesh, Soundarya; Almeida, Shannon D; Hammigi, Sameerana; Radhakrishna, Govardan Katta; Sireesha, Golla; Panneerselvam, Theivendren; Vellingiri, Shangavi; Kunjiappan, Selvaraj; Ammunje, Damodar Nayak; Pavadai, Parasuraman (Drug Research, 2023)
Eukaryotic organisms contain an enzyme family called poly (ADP-ribose) polymerases (PARPs), which is responsible for the poly (ADP-ribosylation) of DNA-binding proteins. PARPs are members of the cell signaling enzyme class. PARP-1, the most common isoform of the PARP family, is responsible for more than 90% of the tasks carried out by the PARP family as a whole. A superfamily consisting of 18 PARPs has been found. In order to synthesize polymers of ADP-ribose (PAR) and nicotinamide, the DNA damage nick monitor PARP-1 requires NAD+ as a substrate. The capability of PARP-1 activation to boost the transcription of proinflammatory genes, its ability to deplete cellular energy pools, which leads to cell malfunction and necrosis, and its involvement as a component in the process of DNA repair are the three consequences of PARP-1 activation that are of particular significance in the process of developing new drugs. As a result, the pharmacological reduction of PARP-1 may result in an increase in the cytotoxicity toward cancer cells.
Keywords: PARPs; DNA repair; Synthetic Compounds; Cancer cells